A Comparison of Five Types of Trail Making Test in Korean Elderly - Jang, Jae-Won (Dement Neurocogn Disord, 2016)
BACKGROUND AND PURPOSE: Previously developed Korean versions of the Trail Making Test (TMT) that replaced the English in part B, has been unsuccessful in Korea. The current study identifies the type of TMT tasks from the among multiple TMT versions, which practically and accurately detects the stage of cognitive decline. METHODS: We applied five TMT versions, which include the original TMT, TMT-Korean letter (TMT-KL), TMT-Korean consonant (TMT-KC), TMT-black and white (TMT-B&W), and TMT-square and circle (TMT-S&C). A total of 168 participants were enrolled: 42 cognitively normal controls (NC), 72 patients with mild cognitive impairment (MCI), and 54 patients with Alzheimer's disease (AD). Two sets of TMT (set "A" including TMT, TMT-KL and TMT-B&W, and set "B" including TMT, TMT-KC, and TMT-S&C) were randomly administered to subjects within the contact of a fixed neuropsychological battery. RESULTS: The completion times of TMT-B and TMT-B&W successfully distinguished NC from MCI and AD. TMT-B&W also showed a high correlation with other neuropsychological tests, and correlated well with the original TMT. The other TMT were frequently not successfully completed, nor could they differentiate the clinical groups. CONCLUSIONS: Among the five TMT tasks, the original TMT and the TMT-B&W appeared to be most sensitive to the degree of cognitive impairment. TMT-B&W showed a pattern consistent with the original TMT; thus, this measure may be optimal in Korean older adults, where familiarity with the English alphabet is questionable.